Clinical neuropathology : text and color atlas - Haberland, Catherine (Demos, 2007)
Divided into fourteen chapters, this book presents an overview of the pathologic and clinical aspects of neurologic diseases. It is useful for practicing neurologists and pathologists, as well as residents and fellows preparing for the neurology and pathology boards.